Trends and outcomes of neoadjuvant radiotherapy compared with postoperative radiotherapy for malignant breast cancer - Fu, Wenyan (Oncotarget, 2018)
BACKGROUND: Although neoadjuvant treatment has become the established approach for women with large primary tumors or locally advanced breast cancer for which immediate surgery is not the best approach, it may also stimulate cancer stem cell self-renewal and facilitate recurrence. We sought to determine the survival outcomes of preoperative radiotherapy (PRRT) compared with postoperative radiotherapy (PORT). MATERIALS AND METHODS: The Surveillance, Epidemiology, and End Results (SEER) registry was queried for patients who were diagnosed with breast cancer and underwent cancer-directed surgery. Survival analyses were performed with Cox proportional hazard regression for both overall survival (OS) and disease-specific survival (DSS), and 1:1 propensity score (PS) matching-adjusted competing risk analyses were conducted for DSS. RESULTS: We first identified 1,111,218 eligible patients in 18 registries from 1973 to 2013 and found that, outside of the Utah registry, sequence patterns other than PORT were rarely used. Thus, we next identified eligible patients registered in Utah (n = 7,042) from 1988 to 2007. The treatment trends shifted abruptly in 1988. Compared with the PORT group, the PRRT group showed significantly higher risks of overall mortality (absolute difference, 22.4%; P < 0.001), breast cancer-specific mortality (absolute difference, 8.6%; P < 0.001), and cardiovascular disease-specific mortality (absolute difference, 11.5%; P = 0.021). Survival differences in treatment sequences were correlated with stage. CONCLUSIONS: Substantial shifts in treatment patterns for malignant breast cancer were identified in Utah. Compared with PORT, PRRT showed significantly worse outcomes. These results could inform future standardized options for radiation sequence with surgery and further clinical trials.